Analisis Uji Kuat Tekan Beton Dengan Perendaman Air dari Daerah Gambut - Apria Brita Pandohop Gawei; Okta Meilawaty; Stephanus Alexsander; Alphario Raymond (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The quality of concrete is greatly influenced by the compressive strength obtained after mixing and curing the test specimens. One important factor in making concrete is the quality of the water used, including its acidity level (pH). Water from peat areas, although abundant, generally has a pH below 7, thus affecting the quality of concrete. This study uses a quantitative descriptive approach to determine the effect of low pH water (5.51) as curing water on the compressive strength of concrete with a planned quality of 23 Mpa. Concrete curing was carried out and tested at the ages of 7, 28, and 90 days. The results show that the average compressive strength of concrete at the age of 7 days obtained a compressive strength of 11.0 Mpa, at the age of 28 days the average increased significantly to 18.4 Mpa, but decreased at the age of 90 days with an average compressive strength of 14.1 Mpa. These findings confirm that the use of water with a low pH as a curing water can also significantly reduce the quality of concrete, so special attention is needed in the selection of water used.